2008
DOI: 10.1063/1.2952054
|View full text |Cite
|
Sign up to set email alerts
|

In situ confocal Raman spectroscopy of lubricants in a soft elastohydrodynamic tribological contact

Abstract: This paper describes an experimental setup that combines friction measurements with in situ confocal Raman microscopy on a lubricating fluid film. The setup allows the determination of film thickness and shear-rate profiles, the position-dependent lubricant composition within the rubbing contact, as well as optical imaging of the contact and its surroundings. The tribological contact can be investigated at continuous rubbing conditions over a range of sliding speeds from 1×10−3to2m∕s. The setup’s capabilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…However using a value of η = 0.15 Pas a good agreement is achieved. Similar work carried out by the authors using optical interferometry [28] and work carried out by Bongaerts et al [29] using Raman spectroscopy to measure film thickness in compliant contacts, Bongaerts et al [29] suggested that the discrepancy between the measured and lower operating viscosity might be due to either an increase in lubricant temperature or to the glycerol adsorbing excess water from the atmosphere. One possibility is heating by the illuminating laser light.…”
Section: Fully Flooded Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…However using a value of η = 0.15 Pas a good agreement is achieved. Similar work carried out by the authors using optical interferometry [28] and work carried out by Bongaerts et al [29] using Raman spectroscopy to measure film thickness in compliant contacts, Bongaerts et al [29] suggested that the discrepancy between the measured and lower operating viscosity might be due to either an increase in lubricant temperature or to the glycerol adsorbing excess water from the atmosphere. One possibility is heating by the illuminating laser light.…”
Section: Fully Flooded Resultsmentioning
confidence: 72%
“…Bongaerts et al [29] successfully demonstrated the use of confocal Raman spectroscopy to measure lubricant film thickness within a compliant, tribological contact lubricated with simple Newtonian fluids and stabilized oil/water emulsions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to optical interferometry, other optical imaging techniques have been reported for the studies of EHL contacts in recent years. Bongaerts et al [35] demonstrated the application of in situ confocal Raman microscopy for friction measurements in EHL contacts. Optical imaging on the EHL contact and the determination of film thickness has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Infrared (IR) absorption spectroscopy [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and Raman spectroscopy [16][17][18] are particularly attractive tools for studying buried interfaces nondestructively. There are many practical and interpretational problems associated with the application of Raman and IR spectroscopy to in-contact studies.…”
Section: Introductionmentioning
confidence: 99%